2013
DOI: 10.1002/ejic.201201189
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive Europium‐Chelate‐Based Silica Nanoparticles as a Probe for Stability, Incorporation Efficiency and Trace Analysis

Abstract: Two luminescent terbium and europium lanthanide chelates were efficiently embedded into silica nanoparticles by using a reverse microemulsion process. The incorporation was achieved without covalent bonding between the lanthanide chelates and the silica matrix. To investigate the efficiency of the incorporation process and the stability of the silica‐encapsulated lanthanide complex, a method based on a radioactive probe was developed; γ‐emitting europium (152) chelates were synthesized and incorporated into si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Moreover [Gd(ebpatcn)(H 2 O)] has a reasonably high stability ( p Gd=13.1) with respect to ligand dissociation providing an additional barrier capable of preventing the release of the toxic aqua ion from the NPs in the absence of covalent binding to the silica matrix. The high stability of the Gd NPs in H 2 O over a pH range of 7–8 with respect to metal leakage over a month period has been confirmed by inductively coupled plasma mass spectrometry (ICPMS) and by optical and radiotracing studies performed on the analogous Eu III and Tb III ebpatcn complexes 11. The value of the luminescence emission lifetime measured for the Tb NPs in H 2 O (1.86(3) ms) is slightly longer than the value measured for the monoaqua [Tb(ebpatcn)(H 2 O)] complex in water (1.60(2) ms, which indicates the presence of only one coordinated water molecule in the encapsulated complex.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover [Gd(ebpatcn)(H 2 O)] has a reasonably high stability ( p Gd=13.1) with respect to ligand dissociation providing an additional barrier capable of preventing the release of the toxic aqua ion from the NPs in the absence of covalent binding to the silica matrix. The high stability of the Gd NPs in H 2 O over a pH range of 7–8 with respect to metal leakage over a month period has been confirmed by inductively coupled plasma mass spectrometry (ICPMS) and by optical and radiotracing studies performed on the analogous Eu III and Tb III ebpatcn complexes 11. The value of the luminescence emission lifetime measured for the Tb NPs in H 2 O (1.86(3) ms) is slightly longer than the value measured for the monoaqua [Tb(ebpatcn)(H 2 O)] complex in water (1.60(2) ms, which indicates the presence of only one coordinated water molecule in the encapsulated complex.…”
mentioning
confidence: 84%
“…Above 500 MHz, r 2 exceeds 150 s −1 m M −1 in the case of the large NPs and even 227 s −1 m M −1 in the case of the small ones. Here, using the Gd III concentration in the solution measured either from the NMR paramagnetic susceptibility shift14 or by ICPMS,11 the NPGd50 were shown to contain about 1,000 [Gd(ebpatcn)(H 2 O)] complexes (see the Supporting Information) so that their relaxivities on a per NP basis are r 1 ≅1,9×10 4 s −1 ⋅(m M of NP) −1 at 50 MHz and r 2 >1,5×10 5 s −1 ⋅(m M of NP) −1 for above 500 MHz. Larger NPs are obtained when a larger number of complexes are incorporated in the NP (see the Supporting Information).…”
mentioning
confidence: 99%
“…Moreover, encapsulation into silica nanoparticles improves the chemical and photostabilities of the loaded species . The remarkable optical properties of lanthanide ions (Ln 3+ ), such as narrow emission bands, high color purity, large Stokes shifts, and long luminescent decay times, have often been combined with the advantageous characteristics of silica nanoparticles . However, the use of Ln 3+ ions as bioprobes is restricted, due to their low molar‐absorption coefficients and UV excitation wavelengths .…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al designed NPs with emission colors from green to red by co-binding different molar ratios of Eu (64) and Tb(64). 183 Wartenberg et al designed their own Tb-Eu co-doped Silica NPs with 72 or 73 as antennas, 184 and proposed a new method to study the efficiency of the incorporation process by using 152 Eu chelates for radioactivity measurements. The effect of Ln-complex encapsulation on the ligand triplet-state energy level was questioned by Eliseeva et al, and [Eu 2 (75) 3 ] binuclear helicates incorporation into Silica NPs was shown to have no impact on it.…”
Section: Nanoscale Accepted Manuscriptmentioning
confidence: 99%